Exploring the Potential of Candida sp. SW4-6 as a Probiotic for Enhancing Water Quality in Aquaculture - Jie-Ying Li; Chun-Hung Liu (Microorganisms)
Aquaculture, a vital industry supplying a significant portion of the world’s seafood, faces challenges such as the deterioration of the aquaculture environment. The objective of this study was to isolate and identify microorganisms with the capacity to eliminate nitrite in water from shrimp ponds and evaluate their potential as probiotics to improve water quality. Additionally, the study also determines the ideal conditions for the probiotic to effectively reduce nitrite-N and ammonia-N. Water samples were collected from four shrimp ponds (SW1, SW2, SW3, SW4) and isolates were obtained. Among all the samples, SW4 was the most effective in reducing the concentration of nitrite-N. Upon further isolation of SW4, the strain SW4-W6 showed significant nitrite-N reduction capabilities compared to the 19 other isolates tested. Through morphological, genetic (ITS sequence), and phylogenetic analyses, strain SW4-6 was identified as Candida sp. The isolation of Candida sp. SW4-6 showed superior nitrite-N and ammonia-N reduction capabilities, with sucrose as the carbon source and complete reduction observed at a C/N ratio of 15–20. Gene expression analysis revealed the up-regulation of nitrite reductase in SW4-6 after inoculation, with significantly higher expression observed with sucrose as the carbon source. Salinity and temperature significantly influenced nitrite-N and ammonia-N reduction by SW4-6, with higher temperatures (30 °C) and 0% NaCl favoring faster reduction rates. Candida sp. SW4-6 emerges as a promising probiotic candidate for aquaculture water quality management due to its efficient nitrite-N and ammonia-N reduction capabilities under optimal conditions. Its virulence profile and ability to thrive across various salinity and temperature conditions further support its potential applicability in aquaculture.